The Effect of Social Anxiety on the Risk of Sexual Victimization via Assertiveness in an Ethnically Diverse Sample - Berg, Samantha K. (Violence against women, 2022)
Preliminary evidence suggests social anxiety may increase the risk of sexual victimization via decreased sexual assertiveness. A sample of 2,043 undergraduate students completed an online survey. Analyses of moderated indirect effects examined whether gender or ethnicity moderated the indirect effect of social anxiety on sexual victimization via sexual assertiveness. No moderation effects were found, but the indirect effect of social anxiety on sexual victimization via sexual assertiveness was significant for all five types of sexual victimization. Clinically, the findings suggest that sexual assault risk reduction programs may be improved by including assertive resistance strategies and behavioral rehearsals.